Перспективы использования электропривода в качестве силовой установки легкобронированной техники - Бондарь, А. И.; Дегтярь, С. М.; Кроленко, А. И.; Мормило, Я. М.; Пилипенко, О. Ю.; Сливар, Е. Я. (НТУ "ХПИ", 2016)
У статті розглянуто застосування електроприводу на виробах вітчизняної легкоброньованої техніки на прикладі БТР-4. Проведено розрахунок потужності тягових акумуляторних батарей, запропоновано функціональну схему електрообладнання бронетранспортера з електроприводом, наведено опис її роботи.

In a paper electric drive application on articles domestic of lightly armoured technicians on an example an armored BTR-4 is considered. Calculation of power of traction storage batteries is carried out, the function chart of an electrical equipment of an armoured personnel carrier with the electric drive is offered, the exposition of its operation is given.
Perspectives of use of the electric drive as a power-plant of lightly armoured technicians
Keywords: транспортные средства; электрическая силовая установка; аккумуляторные батареи; тактико-технические характеристики; БТР; горюче-смазочные материалы; узел трансмиссии